Interaksi Antar Negara Asean Plus Three Terhadap Proses Institusionalisme Second Track Diplomacy: Neat 2009- 2019 - Panjaitan, Arthanami Ekakrisima (Mandala: Jurnal Ilmu Hubungan Internasional, 2020)
This paper aims to answer the question on “ How is the interaction among the ASEAN Plus Three countries in the process of institutionalization of Network of East Asian Think-tanks (NEAT) in The ASEAN Plus Three Regionalism?”. The objective of this research is to get an explanation on the interaction between every country in the ASEAN Plus Three Regionalism on the NEAT institutionalization. This research uses the document research as the study method. As an international institution NEAT is an epistemic community As an epistemic community NEAT holds a variety of research which called as working groups. The result of the working group will be recommended as a policy recommendation. This recommendation will be delivered to the APT leaders to be amendment as a policy. Haas says, as a think tank NEAT directly identifies the state interests and illuminates the decision makers about the salient dimensions of the issue. After that the decision makers in one state may, in turn, influence the interests and behavior of other states. Different with another approachment the actor of an epistemic community is an individual states but still sometimes there tends to be a hegemony of idea in the process of policy decision. In balance with Ikenberry theory that if there is any leading state joins an international institution then that sleading state will ripe another weaker state in order to pursues their interests. This paper suggests that NEAT should enhance the institutionalization as the first official think tank in APT regionalism.